2001
DOI: 10.1038/83667
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of CDH23, encoding a new member of the cadherin gene family, causes Usher syndrome type 1D

Abstract: Usher syndrome type I (USH1) is an autosomal recessive disorder characterized by congenital sensorineural hearing loss, vestibular dysfunction and visual impairment due to early onset retinitis pigmentosa (RP). So far, six loci (USH1A-USH1F) have been mapped, but only two USH1 genes have been identified: MYO7A for USH1B and the gene encoding harmonin for USH1C. We identified a Cuban pedigree linked to the locus for Usher syndrome type 1D (MIM 601067) within the q2 region of chromosome 10). Affected individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
340
1
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 441 publications
(349 citation statements)
references
References 27 publications
1
340
1
7
Order By: Relevance
“…IQGAP2 is expressed inside the cochlea 36 and has been implicated in cadherin-mediated cell adhesion. 37 As cadherin-23 (CDH23) plays an important role in the sensory hair cells, 38 and mutations in CDH23 are responsible for syndromic and nonsyndromic autosomal recessive deafness in humans 39,40 and agerelated hearing loss in inbred mouse strains, 41 this warrants further research. Intriguingly, the SNP rs161927 (P-value 0.000149), that ranked eighth for PC1, was positioned immediately downstream from the metabotropic GRM7 gene.…”
Section: Discussionmentioning
confidence: 99%
“…IQGAP2 is expressed inside the cochlea 36 and has been implicated in cadherin-mediated cell adhesion. 37 As cadherin-23 (CDH23) plays an important role in the sensory hair cells, 38 and mutations in CDH23 are responsible for syndromic and nonsyndromic autosomal recessive deafness in humans 39,40 and agerelated hearing loss in inbred mouse strains, 41 this warrants further research. Intriguingly, the SNP rs161927 (P-value 0.000149), that ranked eighth for PC1, was positioned immediately downstream from the metabotropic GRM7 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The protocadherin LKC is associated with contact inhibition of cell proliferation, and has been suggested as a candidate TSG for colon and liver cancer (Okazaki et al, 2002). Mutations in protocadherin 15 as well as CDH23 have also been implicated in Usher syndrome (Bolz et al, 2001;Di et al, 2001;Siemens et al, 2002), as recently demonstrated in a zebrafish model Sollner et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Waltzer and shaker1 mutants both have disorganized stereocilia bundles caused by mutations in cadherin 23 (Cdh23) and myosin VIIa (Myo7a), respectively Self et al 1998;Di Palma et al 2001;Holme and Steel 2002). CDH23 is mutated in Usher's syndrome type 1D (USH1D) and MYO7A in USH1B patients (Weil et al 1995;Bolz et al 2001;Bork et al 2001). Patients with USH1 are congenitally deaf, have vestibular dysfunction, and develop retinitis pigmentosa (Smith et al 1994).…”
Section: Introductionmentioning
confidence: 99%